SPATIAL MEANINGS OF NA AND SEMANTICALLY RELATED PREPOSITIONS IN MACEDONIAN (Journal of Contemporary Philology, 2018)
The paper presents а contrastive analysis of the spatial meanings of the preposition na and its semantic counterparts in Macedonian. Reviewed here are the contexts in which na assumes similarity of meaning to another preposition. In that respect, a view is presented that the synonymy among prepositions ensues from a shared topology they denote. This necessitates that the preposition in question should code the same position of participants as the preposition of comparison. However, the preposition na shows contextual uniqueness for the functional sense it carries. Whenever contrasted with another preposition in Macedonian, its functional aspect gains salience, whereby na introduces strong functional sense.
Keywords: spatial prepositions; semantic nuance; topology; synonymy